DEVELOPMENT OF PRACTICAL SKILLS IN FOREIGN STUDENTS DURING EDUCATION AT THE DEPARTMENT OF PROPEDEUTICS OF SURGICAL DENTISTRY - I.A. Kolisnyk; A.I. Pankevych; A.M. Hohol; V.M. Novikov; E.Yu. Rezvina; M.A. Korostashova (Український стоматологічний альманах)
The goal of higher education is to produce highly qualified, competitive young professionals capable of innovation, self-improvement, and continuous development. The assimilation of theoretical material, the ability to analyze, search and process the received information are definitely important goals, however, the content of medical education cannot be reduced to only theoretical knowledge, but must ensure the mastery of practical skills. Considering the fact that the education of foreign students is carried out in a distance format due to the military situation in the country, mastering practical skills by these students has certain difficulties.